2011
DOI: 10.1038/leu.2011.128
|View full text |Cite
|
Sign up to set email alerts
|

Genomic profiling in Down syndrome acute lymphoblastic leukemia identifies histone gene deletions associated with altered methylation profiles

Abstract: Patients with Down syndrome (DS) and acute lymphoblastic leukemia (ALL) have distinct clinical and biological features. Whereas most DS-ALL cases lack the sentinel cytogenetic lesions that guide risk assignment in childhood ALL, JAK2 mutations and CRLF2 overexpression are highly enriched. To further characterize the unique biology of DS-ALL, we performed genome-wide profiling of 58 DS-ALL and 68 non-Down syndrome (NDS) ALL cases by DNA copy number, loss of heterozygosity, gene expression, and methylation analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
35
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 37 publications
3
35
0
Order By: Relevance
“…2A), and were not associated with CRLF2 status. This finding is consistent with previous genomic studies in DS-ALL (27,28), and to our knowledge, has not been reported in other cancers, including leukemias.…”
Section: Resultssupporting
confidence: 83%
“…2A), and were not associated with CRLF2 status. This finding is consistent with previous genomic studies in DS-ALL (27,28), and to our knowledge, has not been reported in other cancers, including leukemias.…”
Section: Resultssupporting
confidence: 83%
“…The former frequency is similar to the one described by Heerema et al, 4 whereas the latter is lower than the 5-16% previously reported in DS-ALL. [26][27][28][29][30] Both DS patients in our series are alive in first complete remission more than 9 years after diagnosis. Thus, our data neither support a notable prevalence of DS in HeH patients nor indicate a particularly poor outcome of DSHeH cases.…”
Section: In Cases With 51-67 Chromosomes; 2 Data Missing For Some Varmentioning
confidence: 94%
“…25 Although these genes have not been reported to be deleted in ALL or otherwise associated with this disease, the observed 6p imbalances overlap to some extent with 6p deletions reported in Down syndrome-associated ALL and other histone clusters on 6p have been shown be deleted in pediatric ALL, with methylation arrays suggesting that histone deletions are associated with methylation alterations. 26,27 Thus, HIST1H2BD and HIST1H1E may be added to the growing list of acute leukemia-associated genes, for example DNMT3, EZH2, HOX family, and MLL, that 13 contribute to the leukemogenic process through deregulated CpG methylation or histone modification. [28][29][30][31] Among the other recurrent gene targets, most -CDKN2A, EBF1, ETV6, IKZF1, PAX5, RAG1, and TBL1XR1 -have been thoroughly discussed previously.…”
mentioning
confidence: 99%